Ex vivo resection and renal autotransplantation for the treatment of a large renal vein aneurysm causing recurrent pulmonary embolism and a coexisting vascular malformation: A case report - Özyüksel, Arda; Aktaş, Sema; Çalıs, Elif; Erol, Cengiz; Sevmiş, Şinasi (Sage Publications Inc, 2016)
A 36-year-old young woman with a medical history of recurrent pulmonary embolism and chronic pelvic pain was admitted to our hospital. Contrast-enhanced imaging techniques revealed a large left renal vein aneurysm with a coexisting vascular mass. The patient was operated on electively, and the left kidney was autotransplanted to the right ileac fossa following the ex vivo resection of the vascular mass and the left renal vein aneurysm. Herein, we report an unusual coexistence of a vascular mass and recurrent pulmonary embolism treated successfully with our surgical treatment strategy.
WOS: 000383396700008
PubMed ID: 27334478
Keywords: Renal Vein; Aneurysm; Vascular Malformation; Pulmonary Embolism; Renal Autotransplantation